Teaching Caregivers to Support Social Communication: Results From a Randomized Clinical Trial of Autistic Toddlers - Roberts, Megan Y; Stern, Yael S; Grauzer, Jeffrey; Nietfeld, Jennifer; Thompson, Suzanne; Jones, Maranda; Kaat, Aaron J; Kaiser, Ann P (American journal of speech-language pathology, 2023)
Studies of early caregiver-mediated interventions targeting social communication of young autistic children have yielded variable child outcomes. This study examined the effects of combining two caregiver-mediated interventions on caregiver strategy use and child social communication and language outcomes. This was a multisite parallel randomized controlled trial. Participants included 120 caregivers and their autistic children between 24 and 36 months of age. Dyads were randomly assigned to receive a hybrid intervention that combined Enhanced Milieu Teaching (EMT) and Joint Attention, Symbolic Play, Engagement, and Regulation (JASPER) or to a behavior management control condition, each delivered over 6 months. Caregivers in the JASP-EMT group received twice-weekly, in-home, and hour-long sessions. Outcomes were measured at baseline, the end of intervention (T1), and 6 months later (T2) and included a naturalistic language sample procedure, standardized measures, and caregiver report measures. This trial was registered at clinicaltrials.gov (NCT02595697). Child outcomes did not differ between conditions at T1 or T2 for child primary (social communication) or secondary (language, play, and autism symptoms) outcomes. Relative to control group caregivers, intervention group caregivers demonstrated significantly higher use of JASP-EMT strategies at T1 and T2, with the exception of two strategies (Responsiveness and Matched Responsiveness), which were used significantly more by control group caregivers. Neither autism severity nor baseline caregiver responsiveness moderated outcomes. Post hoc analyses revealed significant correlations between specific strategies and all child outcomes. Twice-weekly caregiver-mediated intervention that taught caregivers of autistic children to use social communication support strategies did not yield significant child outcomes. Future studies should examine possible sources for the lack of main effects including unexpected differences in linguistic features of caregiver input, changes in control group caregiver behavior, and insufficient intervention dosage. https://doi.org/10.23641/asha.21714278.